Oxygen saturation before and after mechanical thrombectomy and functional outcome in patients with acute ischemic stroke - Yu, Shuhong; Yu, Shuai; Zhang, Hang; Dai, Qingyong; Huang, Hao; Luo, Yi; Guo, Zhiliang; Xiao, Guodong (Frontiers in Cardiovascular Medicine, 2022)
Background and Purpose: There is a lack of effective neuroprotection to break the ceiling effect of mechanical thrombectomy (MT) at present, one of the most promising is normobaric oxygen treatment. However, the impacts of oxygen saturation before and after MT on clinical outcomes in patients with acute ischemic stroke (AIS) remains unclear. We aimed to determine the influence of preoperative and postoperative oxygen saturation on three-month poor outcome in AIS patients. Methods: A total of 239 consecutive stroke patients with successful recanalization by MT between May 2017 and March 2021 were analyzed. Recordings of oxygen saturation were measured non-invasively by pulse oximetry, which were measured at baseline and continually measured after MT. AIS patients were divided into 4 groups according to the median levels of oxygen saturation before and after MT: HL (higher preoperative oxygen saturation and lower postoperative oxygen saturation), LL (lower preoperative oxygen saturation and lower postoperative oxygen saturation), HH (higher preoperative oxygen saturation and higher postoperative oxygen saturation) and LH (lower preoperative oxygen saturation and higher postoperative oxygen saturation). Regression analysis was used to assess the association of preoperative and postoperative oxygen saturation with three-month poor outcome (modified Rankin Scale score of 3 to 6 ) in AIS patients. Results: The decreased preoperative oxygen saturation level was associated with increased risk of poor outcome (odds ratio, 0.85; 95% CI, 0.73–0.98; P=0.0293). However, postoperative oxygen saturation has the opposite effect on poor outcome (odds ratio, 1.60; 95% CI, 1.13–2.27; P=0.0088). In addition, LH was associated with a 6.35-fold increase in the risk of poor outcome in comparison to HL (odds ratio, 0.10; 95% CI, 1.97–20.52; P trend = 0.0014). CONCLUSION: The preoperative and postoperative oxygen saturation have different influences on three-month poor outcome in AIS patients with successful recanalization by MT.